Karakteristik Peserta Didik: Sebuah Tinjauan Studi Kepustakaan - Maman Maman; Moch. Syamsuri Rachman; Irawati Irawati; Hasbullah Hasbullah; Juhji Juhji (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2021)
This study aims to describe the characteristics of students in an educational institution. This study uses literature studies. The data obtained from various references such as books and scientific articles are collected and analyzed related to students. The study of Hadiths is also done as an effort to sharpen discussions related to learners. A qualitative approach is done by descriptive and argumentative analysis. The results of the study that students as one of the main components in education must be known the level of competence, characteristic differences, and rights and obligations. Educational activities conducted through the learning process must lead them to achieve a life goal that has been outlined in Islamic teachings